2008
DOI: 10.1094/pdis-92-3-0483b
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Wilt of Mulberry (Morus alba) Caused by Enterobacter cloacae in China

Abstract: In August of 2006, a new bacterial disease was noted in Hangzhou mulberry orchards of Zhejiang Province, China where bacterial wilt of mulberry caused by Ralstonia solanacearum was previously reported (3). In the summer, the disease caused severe wilt, especially on 1- or 2-year-old mulberry plants, that resulted in premature plant death. Leaf wilt symptoms generally started on older leaves at the bottom of the plant and spread to the younger leaves. The leaves of infected plants became withered and dry, turne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…General and other biological features from Brenner et al 1986 andHoffmann et al 2005. conducted, none of the popular mulberry cultivars, including Nongsang, Husang and Heyebai, are resistant to this disease. Strains of the MWD pathogen were initially reported as E. cloacae (Wang et al 2008), a common species surviving in diverse habitats and ecological niches, and existing widely in soil, water, plants, insects and animals (Nishijima et al 2004). Characterization of the four additional MWD strains in this study revealed they belong to Enterobacter but are not E. cloacae.…”
Section: Additional Biological Featuresmentioning
confidence: 75%
See 2 more Smart Citations
“…General and other biological features from Brenner et al 1986 andHoffmann et al 2005. conducted, none of the popular mulberry cultivars, including Nongsang, Husang and Heyebai, are resistant to this disease. Strains of the MWD pathogen were initially reported as E. cloacae (Wang et al 2008), a common species surviving in diverse habitats and ecological niches, and existing widely in soil, water, plants, insects and animals (Nishijima et al 2004). Characterization of the four additional MWD strains in this study revealed they belong to Enterobacter but are not E. cloacae.…”
Section: Additional Biological Featuresmentioning
confidence: 75%
“…isolates R2-2, R6-2, R11-2 and R18-2 (typical symptoms marked by arrows) ; H, I, J. Seedling symptoms in type strain LMG2683 (H), R11-2 (I) and R18-2 (J) inoculation; CK indicates control Enterobacter were obtained from GenBank (Stephan et al 2007;Stephan et al 2008). R3-3 and R8-2 are the E. cloacae strains isolated previously (Wang et al 2008). Neighbour-joining phylogenetic distance trees were constructed based on the 16S rDNA sequence data (Fig.…”
Section: Pcr Amplification and Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies done in China, on the basis of Biolog metabolic profiles, fatty acid methyl ester analysis, and sequence analysis of the partial 16S rDNA and rpoB genes, reported a novel species of pathogen and named it as Enterobacter mori. It was also observed that another known species called Enterobacter asburiae also caused mulberry wilt disease (Wang et al 2008). Similarly, in Zingiberaceae family, Curcuma alismatifolia (pathumma), an ornamental plant with a worldwide market, was reported to be susceptible to bacterial wilt caused by Enterobacter sp.…”
Section: Discussionmentioning
confidence: 98%
“…In the summer of 2006, a severe bacterial wilt was noted in mulberry orchards in Hangzhou, Zhejiang Province, China. Our laboratory isolated the pathogen and identified it as an Enterobacter species (6)(7)10). Later, DNA-DNA hybridization, fatty acid analysis, and phylogenetic analysis suggested that it was a new species in the genus Enterobacter (9).…”
mentioning
confidence: 99%